Toxicity effects of fungicide residues on the wine-producing process - Calhelha, Ricardo C. (2008)
We report the detection of several fungicide residues (Dichlofluanid, Benomyl, Iprodione, Procymidone and Vinclozolin) in red and white bottled wines from two Portuguese wine-producing zones. Studies were done in order to evaluate the active compound transfer percentage from grapes to the final product along fermentation process. We also investigated their effects in Saccharomyces and non-Saccharomyces yeasts as well as their influence on the physical, chemical and organoleptic wine properties. All the tested fungicides had a negative effect on in vitro yeast growth, with Dichlofluanid and Benomyl being the most toxic. Zygosaccharomyces rouxii and Saccharomyces cerevisiae were the most resistant yeasts while Rhodotorula glutinis was the most susceptible. Microvinification experiments carried out in the presence of fungicides produced wine samples with unaltered physical, chemical and organoleptic properties, though Benomyl, a slight delay in the initiation of fermentation process was observed.